Producing Superphosphate with Sewage Sludge Ash: Assessment of Phosphorus Availability and Potential Toxic Element Contamination - Yawen You; Jakob Klein; Tobias Edward Hartmann; Peteh Mehdi Nkebiwe; Huaiyu Yang; Wei Zhang; Xinping Chen; Torsten Müller (Agronomy, 2021)
Recovering and recycling phosphorus (P) from sewage sludge ash (SSA) for the purpose of P fertilizer production contributes to reducing the input of mined phosphate-minerals and closing of the P cycle. However, direct use of SSA as fertilizer is often a questionable strategy due to its low nutrient use efficiency. In addition, the environmental risk potential of utilizing SSA in agriculture is still unclear, in particular potential toxic element (PTE) contamination. In this study, a mixture of SSA and rock phosphate was used at lab-scale superphosphate (SP) production. P availability of the final product and PTE contamination (Cd, Cr, Cu, Zn, Pb, Ni) in soil and crop was investigated through maize (Zea mays L.) cultivation. Results showed that the application of SP that was produced by 25% SSA replacement did not affect the growth, P uptake, and PTE content in aboveground maize compared to the application of SP produced without SSA replacement. However, significant inputs of SP with SSA replacement may decrease the solid-soil solution partitioning of Cu, Ni and Pb in the long-term. Separation of municipal/industrial sludge and PTE removal technology are necessary to be implemented prior to the use of SSA as a secondary raw material in P-fertilizer production.